Menopause and Climacteric. Substituted Hormonal Treatment. Its indications, guidelines and safety. - Rubén Darío García Núñez; María Aurelia San Juan Bosch; Mikhail Benet Rodríguez; Irene E. Delgado Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
An updated revision was carried out about climateric and menopause period and its substituted hormonal treatment when it is necessary. The indications of the substituted hormonal therapy, its main contraindication and the directions of the treatment are shown.